Control of extreme brominated persistent organic pollutant emissions from start-ups of waste-to-energy incinerators. (15th April 2022) - Yang, Hsi-Hsien; Cheruiyot, Nicholas Kiprotich; Lin, Chitsan; Wang, Lin-Chi
Abstract: Unlike chlorinated persistent organic pollutants (Cl-POPs), few studies have investigated the emissions of brominated POPs (Br-POPs), including polybrominated dibenzo- p -dioxins and dibenzofurans (PBDD/Fs), polybrominated biphenyls (PBBs), and polybrominated diphenyl ethers (PBDEs), from start-up processes of municipal solid waste incinerators (MSWIs). Presently, there are no studies published on Br-POP control during this period. This study found that start-up processes could contribute to at least 27%, 55%, and 2% PBDD/F, PBB, and PBDE emissions of an entire year of MSWI operations. High PBDD/F and PBDE emission rates were observed at the beginning of the start-up, indicating that control measures should be conducted before or at the beginning of the start-ups. PBBs behaved like Cl-POPs with high emission rates observed at the POP-formation temperature window (250–450 °C). Unlike Cl-POPs, inhibiting adsorptive memory effects by cleaning the accumulated ash was the most effective control strategy for PBDD/F and PBDE emissions, accounting for 72.8% and 51.3% of total reductions, respectively. Contrarily, inhibiting Br-POP formation by cleaning the accumulated ash and shortening the residence time of the flue gas in 250–450 °C contributed to the highest PBB reduction (67.5%). Overall, the control strategies reduced PBDD/F and PBB emissions by >97% and PBDEs by 61%. This study shows that PBDD/Fs and PBDEs behave differently from their chlorinated equivalents and require different control strategies. In conclusion, the control strategies proposed can reduce Br-POP emissions during start-up successfully, and they require no modifications to existing control devices. Graphical abstract: Image 1 Highlights: High PBDD/F and PBDE concentrations were observed at the beginning of the start-up. PBBs behaved similarly to chlorinated counterparts. The control strategies reduced PBDD/F and PBB emissions by >97% and PBDEs by 61%. These strategies require no modifications to existing control devices.